Analisis Hasil Audit Kepatuhan Dana Kampanye Partai Politik Sebagai Tingkat Transparansi Pemilihan Umum - Aulia Rahma Az zahra; Hero Priono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study was conducted to gain an understanding of the results of the implementation of campaign finance compliance audits of political parties based on PKPU Number 18 of 2023 and to assess the level of transparency in general elections in Indonesia. The approach used is a qualitative method with data collection techniques from the results of compliance audits and conducting interviews with senior auditors to find out views regarding the level of transparency in general elections. The findings in this study provide knowledge that not all political parties comply with the regulations that have been set. This study also explains that the supervision carried out in the reporting and management of campaign funds is still not optimal. Strict supervision and increased education and training for political parties can help maximize the level of transparency in general elections.